Diagnostic accuracy of loop-mediated isothermal amplification as a near-patient test for meningococcal disease in children: an observational cohort study. Issue 5 (May 2015) - Bourke, Thomas W; McKenna, James P; Coyle, Peter V; Shields, Michael D; Fairley, Derek J
Summary: Background: Diagnosis of meningococcal disease relies on recognition of clinical signs and symptoms that are notoriously non-specific, variable, and often absent in the early stages of the disease. Loop-mediated isothermal amplification (LAMP) has previously been shown to be fast and effective for the molecular detection of meningococcal DNA in clinical specimens. We aimed to assess the diagnostic accuracy of meningococcal LAMP as a near-patient test in the emergency department. Methods: For this observational cohort study of diagnostic accuracy, children aged 0–13 years presenting to the emergency department of the Royal Belfast Hospital for Sick Children (Belfast, UK) with suspected meningococcal disease were eligible for inclusion. Patients underwent a standard meningococcal pack of investigations testing for meningococcal disease. Respiratory (nasopharyngeal swab) and blood specimens were collected from patients and tested with near-patient meningococcal LAMP and the results were compared with those obtained by reference laboratory tests (culture and PCR of blood and cerebrospinal fluid). Findings: Between Nov 1, 2009, and Jan 31, 2012, 161 eligible children presenting at the hospital underwent the meningococcal pack of investigations and were tested for meningococcal disease, of whom 148 consented and were enrolled in the study. Combined testing of respiratory and blood specimens with use of LAMP was accurate (sensitivity 89% [95% CI 72–96], specificity 100% [97–100], positive predictive value 100% [85–100]; negative predictive value 98% [93–99]) and diagnostically useful (positive likelihood ratio 213 [95% CI 13–infinity] and negative likelihood ratio 0·11 [0·04–0·32]). The median time required for near-patient testing from sample to result was 1 h 26 min (IQR 1 h 20 min–1 h 32 min). Interpretation: Meningococcal LAMP is straightforward enough for use in any hospital with basic laboratory facilities, and near-patient testing with this method is both feasible and effective. By contrast with existing UK National Institute of Health and Care Excellence guidelines, we showed that molecular testing of non-invasive respiratory specimens from children is diagnostically accurate and clinically useful. Funding: Health and Social Care Research and Development, Public Health Agency, Northern Ireland.